(untitled) (Medical Forum Monthly, 2020)
Objective: This study was conducted to determine the frequency of post-operative complications of omentoplasty in patients with perforated duodenal ulcers. Study Design: Descriptive Study. Place and Duration of Study: This study was conducted at the Department of General Surgery, Bolan Medical Complex Hospital Quetta from September 2018 to February 2020. Materials and Methods: A total number of 261 patients with diagnosis of duodenal peptic ulcers having age 18 to 60 years were included in this study. Closure of perforated duodenal ulcers was done by giving a midline laparotomy incision. Following identification of the perforation area, extensive peritoneal toilet was performed using warm saline. Patch repair was then done in standard fashion. Mass closure of fascia was performed using omental patch with 1/0 suture and interrupted closure to skin incision subsequently with proline sutures. Diagnosis of post-operative complications of omentoplasty e.g. organ space infections, sepsis and death rate were noted in the post-operative period. Results: Mean age of patients was 40.42±9.61 years. There were 144 (55.17%) male and 117 (44.83%) female patients. Mean duration of symptoms of patients was 9.49±4.38 hours. Organ space infections occurred in 16 (6.13%) patients, sepsis in 10 (3.83%) patients and mortality in in 23 (8.81%) patients. Conclusion: Omental patch repair is simple to perform and yet reliable for closure of much large perforations. Only Patch closure is sufficient for duodenal perforations considering low complications rate. In present study frequency of complications was comparable as mentioned in previous studies.